Treatment Response, Survival, and Safety of Transarterial Chemoembolization With CalliSpheres® Microspheres Versus Conventional Transarterial Chemoembolization in Hepatocellular Carcinoma: A Meta-Analysis - Liang, Bin; Makamure, Joyman; Shu, Shenglei; Zhang, Lijie; Sun, Tao; Zheng, Chuansheng (Frontiers in Oncology, 2021)
Background Drug-eluting embolic transarterial chemoembolization (DEE-TACE) is an advance in TACE technique. However, at present there is insufficient evidence to support that DEE-TACE is superior to conventional TACE (cTACE) for hepatocellular carcinoma (HCC). The aim of this meta-analysis is to evaluate the efficacy and safety of TACE with CalliSpheres® microspheres (CSM-TACE) compared with cTACE in patients with HCC. Data Sources PubMed, Embase, Web of Science, CNKI and Wanfang Databases were searched to identify relevant articles published before March 26, 2020. The data regarding treatment response, survival profile, adverse events and liver function indexes were retrieved. Results A total of 16 studies with 1454 HCC patients (722 treated with CSM-TACE and 732 with cTACE) were included. Patients receiving CSM-TACE had higher 1-month complete response (CR), objective response rate (ORR), disease control rate (DCR) (odds ratio (OR): 2.00, 95% confidence interval (95% CI): 1.29–3.09; OR: 2.87, 95% CI: 2.15–3.83; OR: 2.01, 95% CI: 1.37–2.95, respectively), 3-month CR, ORR, DCR (OR: 4.04, 95%CI: 2.46–6.64; OR: 3.39, 95%CI: 2.45–4.70; OR: 1.71, 95%CI: 1.14–2.55 respectively), and 6-month CR, ORR, DCR (OR: 4.02, 95%CI: 2.26–7.16; OR: 3.00, 95%CI: 2.05–4.38; OR: 2.66, 95%CI: 1.70–4.16 respectively) than those treated with cTACE. Furthermore, CSM-TACE exhibited a trend toward improved progression free survival (hazard ratio (HR): 0.86, 95%CI: 0.67–1.11) and overall survival (HR: 0.79, 95%CI: 0.59–1.07) over cTACE although these differences did not reach statistical significance. In terms of safety, the two TACE treatments showed similar post-treatment pain (OR: 0.84, 95%CI: 0.55–1.28), fever (OR: 0.99, 95%CI: 0.60–1.63), nausea/vomiting (OR: 0.84, 95% CI: 0.60–1.17), as well as 1-month follow-up alanine aminotransferase (Mean difference (MD): −3.66, 95%CI: −10.38–3.07), aspartate aminotransferase (MD: −2.30, 95%CI: −8.91–4.31) and total bilirubin (MD: −0.15, 95%CI: −2.26–1.96). Conclusion CSM-TACE displays superior treatment response, non-inferior survival profile and safety over cTACE in HCC patients.